A Project feasibility study on KSC Herbal Tea - Avelino, Leah Mariel D.; Ay-Ad, Ana Melissa E.; Escudero, Ma. Bernadette G.; Nerida, Kristine Q. (College of Engineering, 1999)
The product of concern is the KSC Herbal Tea. Invented and named by Mrs. Clarita Baniqued, the product consists of dried leaves from a medicinal plant called Orthosiphon Aristatus. It is used to treat kidney related diseases specifically kidney stones, thus the acronym KSC for Kidney Stone Crusher. From the Market Study, It was established that the target market would be individuals with kidney related diseases. The product's market area of dispersion would be in the National Capital Region. Market Shares for the first five years would be 9.88% for the year 2000m 10.68% for 2001, 11.55% for 2002, 12.49% for 2003 and 13.51% for 2004. The product is priced at P105 per tea bag and would also be sold in boxes of 20's which would have a total cost of P2,100, A total marketing budget of P 2,383,800 would be allocated for product promotions. The technical study meanwhile, explains the major processes of the product. These include Planting, Harvesting, Processing and Packaging. A monthly production of 30,000 tea bags is to be produced for the first year, with an additional 6,000 tea bags for each of the first three months, which would serve as inventory. From this, production planning, equipment, machinery, and tooling requirements were determined. Suppliers were evaluated and a supplier for each of these was chosen. Capacity planning dictat3ed that there would be two sites needed - a farm site and an office site. The farm, with only 12,000 square meters to be used in the first year, is to be located in San Carlos, Pangasinan. A laboratory is to be constructed near the farm. The office site would be in Cititowers, located at 810 Aurora Blvd. In Cubao. A total pre-operating and production cost of P13,545,452.97 would be needed for the first year of operations. The organization and management study proves that a company would be the best form of ownership. The name of the company would be KSC Manufacturing Inc. The board of directors will be followed by a general manager, which leads the other managers of the different departments such as purchasing, operations, finance, accounting, human resources, and marketing and sales. Job descriptions, qualifications and salaries including benefits are discussed in this section. Based on the total project cost, the financial study was discussed. Major assumptions had to be taken into consideration. The equity would be equal to an a mount of P5,106,251.47, while the loan which is to be obtained from the Philippine National Bank is equal to P3,404,167.65 The financial statements composed of the pro-forma income statement, cash flows, and the pro-forma balance sheet all reflected positive results which proved that the company is profitable. Numerous tests also showed the same, with the Net Present Value of the Company equal to P100,797,445.7 and the Internal Rate of Return at 312%. The payback period was also determined to be immediately a year after operations. The social profitability analysis showed that the company also contributes to the market, the local government and national government. These quantitative benefits include providing more jobs, offering an alternative medicine which is all natural, of high quality and of competitive price, generating profit through the utilization of locally made raw materials and utilities, and the revenues due to municipal, income and value added taxes. The production of the KSC Herbal Tea also contributes to the industrialization of San Carlos, Pangasinan and facilitates the promotion and growth of alternative medicine in the country. In summarizing all the results of the marketing, technical, organizational and management, financial and the social profitability analyses, it was proven that the project is feasible.